No apparent association between bipolar disorder and cancer in a large epidemiological study of outpatients in a managed care population. (March 2018) - Kahan, Natan R.; Silverman, Barbara; Liphshitz, Irena; Waitman, Dan-Andrei; Ben-Zion, Itzhak; Ponizovsky, Alexander M.; Weizman, Abraham; Grinshpoon, Alexander
Abstract : An association between bipolar disorder (BD) and cancer risk has been reported. The purpose of this study was to investigate this association through linkage analysis of a national HMO database and a national cancer registry. All members of the Leumit Health Services (LHS) HMO of Israel from 2000 to 2012 were included. Members with a recorded diagnosis of BD and a record of at least one written or dispensed prescription for pharmacotherapy for treatment of BD were classified as patients with BD. We linked the LHS population with the Israel National Cancer Registry database to capture all cases of cancer reported. Standardized incidence ratios (SIRs) for cancer in the BD population as compared with non-BD LHS members were calculated. A total of 870 323 LHS members were included in the analysis; 3304 of whom met the criteria for inclusion in the BD arm. We identified 24 515 and 110 cancer cases among members without BD and with BD, respectively. Persons with BD were no more likely than other HMO members to be diagnosed with cancer during the follow-up period [SIR, males=0.91, 95% confidence interval (CI): 0.66–1.22; SIR, females=1.15, 95% CI: 0.89–1.47]. Sensitivity analysis using different criteria for positive BD classification (lithium treatment alone or registered physician diagnosis) had no effect on the estimate of cancer risk. A nonstatistically significant association between breast cancer and BD among women was observed (SIR=1.24, 95% CI: 0.79–1.86). These findings do not corroborate previously reported associations between BD and elevated cancer risk.